MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN MAKE A MATCH MATERI BILANGAN PECAHAN PADA SISWA KELAS IV DI SD SWASTA ABDI SUKMA KECAMATAN MEDAN JOHOR - Tiara Safitri Tanjung; Ulian Barus (STKIP Subang, 2023)
This research aims to determine learning through: (1) student learning outcomes before using the make a match learning model in Mathematics subjects in class IV of Abdi Sukma Private Elementary School, Medan Johor District. (2) Application of the make a match learning model in mathematics subjects in class IV of Abdi Sukma Private Elementary School, Medan Johor District. (3) Student learning outcomes after using the make a match learning model in Mathematics subjects in class IV of the Abdi Sukma Private Elementary School, Medan Johor District. The type of research used is Classroom Action Research (PTK) with the subjects of this research being fourth grade students at Abdi Sukma Private Elementary School, Medan Johor District. Based on the research results, it can be concluded that the results before implementing the make a match learning model obtained an average teacher activity result of 83.32% and an average student activity result of 80.08% and an average student learning result of 70%. Based on the results above, it can be concluded that the use of the make a match learning model can improve student learning outcomes in mathematics subjects, the material of recognizing Roman number symbols in class IV D Swasta Abdi Sukma, Medan Johor District.